Dexel-Based Simulation of Directed Energy Deposition Additive Manufacturing - Volker Böß; Berend Denkena; Marc-André Dittrich; Talash Malek; Sven Friebe (Journal of Manufacturing and Materials Processing, 2021)
Additive manufacturing is typically a flexible alternative to conventional manufacturing processes. However, manufacturing costs increase due to the effort required to experimentally determine optimum process parameters for customized products or small batches. Therefore, simulation models are needed in order to reduce the amount of effort necessary for experimental testing. For this purpose, a novel technological simulation method for directed energy deposition additive manufacturing is presented here. The Dexel-based simulation allows modeling of additive manufacturing of varying geometric shapes by considering multi-axis machine tool kinematics and local process conditions. The simulation approach can be combined with the simulation of subtractive processes, which enables integrated digital process chains.